The Impact of Transformational Leadership, Organizational Climate, and Work Engagement on Employee Organizational Citizenship Behavior at PT Kofuku Plastic Indonesia - Heri Irawan, Vicky; Septyarini, Epsilandri; Syafwan Lysander, Mohammad Ahyar (Amkop Management Accounting Review (AMAR), 2025)
This study aims to determine the effect of transformational leadership, organizational climate, and work engagement on organizational citizenship behavior. The sampling technique used was saturated sampling. The sample size was 50 employees. This study is quantitative and utilizes primary data. The data analysis method used was multiple linear regression analysis using SPSS version 23. The data analysis techniques used to answer the above hypothesis were multiple regression analysis, t-test, f-test, and coefficient of determination. The results of this study indicate that transformational leadership has a significant effect on organizational citizenship behavior with a value of 0.000 < 0.010, organizational climate has a significant effect on organizational citizenship with a significant value of 0.005 < 0.010, and work engagement has a significant effect on organizational citizenship with a significant value of 0.004 < 0.010